2017
DOI: 10.1186/s41043-017-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics and psychosocial consequences of sickle cell disease: the case of patients in a public hospital in Ghana

Abstract: BackgroundSickle cell disease (SCD) is of major public health concern globally, with majority of patients living in Africa. Despite its relevance, there is a dearth of research to determine the socio-demographic distribution and psychosocial impact of SCD in Ghana. The objective of this study was to examine the socio-demographic distribution and psychosocial consequences of SCD among patients in Ghana and to assess their quality of life and coping mechanisms.MethodsA cross-sectional research design was used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
(43 reference statements)
6
12
2
1
Order By: Relevance
“…With respect to gender, we observed an equal distribution of males and females (50%) among subjects in steady state group but a slight increase of females than males in crisis group (56.7%). This finding is in accordance with some pre-Open Journal of Blood Diseases vious reports [22] [24] [26]. This observation may be due to the fact that females generally report or complain more than males when they are suffering from different types of illnesses [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to gender, we observed an equal distribution of males and females (50%) among subjects in steady state group but a slight increase of females than males in crisis group (56.7%). This finding is in accordance with some pre-Open Journal of Blood Diseases vious reports [22] [24] [26]. This observation may be due to the fact that females generally report or complain more than males when they are suffering from different types of illnesses [27].…”
Section: Discussionsupporting
confidence: 92%
“…Approximately Our study showed that majority of the participants were aged 5 years and above, with 80% in steady, 50% in crisis. The age group of our cohort of SCD subjects in this study is similar to subjects studied in previous reports [21] [22] [23] [24]. Life expectancy of SCA patients is reduced considerably among younger children and older people.…”
Section: Discussionsupporting
confidence: 73%
“…These tools are a form of living communication between the devotee and a God, imagined as personal and experienced as present. This communication reflects the form of social human relationships (22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…First time stroke in children with SCD has been found to be highest in early childhood that is from 2-5 years and decreases in incidence from 10-19 years (Ohene-Frempong et al, 1998). Furthermore, it has been recently noted that the incidence of stroke in SCD patients aged over 29 years is increased and hence life expectancy is reduced for this group and the very young (Adzika, Glozah, Ayim-Aboagye, & Ahorlu, 2017 The complications lead to frequent and prolonged admissions (Jacob et al, 2005 Long term hospitalisation, during schooling or work time, influenced stability and opportunities to be a regular student or employee. Absenteeism due to the complications of the disease would also undermine performance.…”
Section: The Mother Is the One Who Will Suffer When The Child Ismentioning
confidence: 99%
“…Delay in education is reported to be significantly affected by SCD complications and hospitalisation (Amr et al, 2011). Thus, the disease impacted on many of the basic resources for life, such as intellectual, work, and income (Adzika et al, 2017). For example, a stroke can affect cognitive skills, and thus the ability of patients with sickle cell to engage in learning.…”
Section: The Mother Is the One Who Will Suffer When The Child Ismentioning
confidence: 99%